2010
DOI: 10.1111/j.1365-2095.2009.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal starvation time before blood sampling to get baseline data on several blood biochemical parameters in Amur sturgeon, Acipenser schrenckii

Abstract: This study tested the hypothesis that different starvation time for fish before blood sampling can influence the result of plasma biochemical analysis. Glucose (GLU), total cholesterol (CHOL), triglyceride (TGL) and total protein (TP) in the plasma of juvenile Amur sturgeon (Acipenser schrenckii) were measured after different starvation duration (0, 0.5, 1, 2 and 3 days). Starvation time had a significant influence on plasma GLU, CHOL, TGL and TP concentrations (P < 0.05). Plasma GLU and TP concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Glucose showed a significant decrease at these times, but lipids may also be used for energy production, suggesting that their circulating levels increased to supply energy during the secondary stress response and probably fasting. Similarly, Shi et al (2010) showed a significant increase in serum cholesterol and triglyceride levels accompanied by a significant decrease in serum glucose levels in fasted Amur sturgeon, A. schrenckii.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Glucose showed a significant decrease at these times, but lipids may also be used for energy production, suggesting that their circulating levels increased to supply energy during the secondary stress response and probably fasting. Similarly, Shi et al (2010) showed a significant increase in serum cholesterol and triglyceride levels accompanied by a significant decrease in serum glucose levels in fasted Amur sturgeon, A. schrenckii.…”
Section: Discussionmentioning
confidence: 81%
“…Fish were not fed 24 h before stress, and hypoglycaemia may have occurred at 72 h poststress. Similarly, Shi, Zhuang, Zhang, Chen, Xu, Feng and Huang () showed a significant decrease (~2‐fold) in serum glucose levels following a 72 h fasting in Amur sturgeon, Acipenser schrenckii .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Starvation or undernutrition during life cycle of aquatic organisms can occur either in the natural environment or under culture conditions due to spatial and temporal patchiness of feed resources (Zhang, Zhang, Li, & Gao, ). In recent years, it was determined that starvation has an effect on growth (Eroldogan, Kumlu, Kırıs, & Sezer, ; Li et al., ), oxidative stress parameters (Furne et al., ), some antioxidant indexes (Li et al., ), oxygen consumption, metabolic enzymes (Powell & Watts, ), blood biochemical parameters (Shi et al., ), immune system (Verghese, Radhakrishnan, & Padhi, ), protein (Garcia‐Garrido, Hachero‐Cruzado, Rosas, & Domingues, ; Muhlia‐Almazan, Sanchez‐Paz, Garcia Carreno, Peregrino‐Uriarte, & Yepiz‐Plascencia, ), lipid and fatty acids (Cicek & Kumlu, ; Durazo‐Beltran, Viana, D'Abrama, & Toro‐Vazquez, ; Morillo‐Velarde, Valverde, Llinares, & Garcia, ; Smith, Thompson, Ritar, & Dunstan, ) and reproduction (Chatzifotis, Papadaki, Despoti, Roufidou, & Antonopoulou, ) of aquatic organisms. At present, the effects of starvation in Astacus leptodactylus have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…No presente estudo, as amostragens de sangue foram realizadas em tempo inferior ao tempo máximo estabelecido na literatura, considerando-se os intervalos entre a captura e o final da punção caudal. Os procedimentos de coleta são necessários para os estudos relacionados aos parâmetros fisiológicos em peixes, entretanto deve-se destacar a dificuldade observada na sua realização, em função do pequeno porte, do reduzido calibre dos vasos sanguíneos e da pouca quantidade de amostra coletada na espécie estudada (EAMES et al, 2010;SHI et al, 2010 (BARCELLOS et al, 2001;LIMA et al, 2006;FAGUNDES;URBINATI, 2008). Em exemplares de Sparus aurata L foi observado aumento da glicose e do cortisol após exposição aérea de três minutos, e para espécie Perca fluviatilis L elevação do cortisol após apenas um minuto de exposição a este agente estressor (ARENDS et al, 1999;ACERETE et al, 2004).…”
Section: Resultsunclassified